LINGVISTIK KOMPETENSIYAGA DOIR TA’LIM MAZMUNI VA STRUKTURASINI TAKOMILLAShTIRISh - Tajbenova, S.S. (SCIENCE and SOCIETY, 2025)
This article focuses on improving the content and structure of linguistic competence education in primary school native language lessons.